A new species of Naematelia (Tremellales, Basidiomycota) from India - Thomas, Anjitha; Kumar, T.k. Arun (Phytotaxa, 2024)
A new species of Naematelia, N. encephaloidea, was collected and described from Silent Valley National Park, Kerala State, India. It is characterized by two types of swollen cells in trama, thick-walled, non-germinating, and thin-walled, germinating; thick-walled, globose conidia; inflated cells in the trama; lack of hyphidia. The identity of the new species is confirmed by morphological characteristics, and ITS and LSU sequence based molecular study. A key to the known Naematelia species is also provided.